Global economic prospects and the developing countries 1997 - World Bank (Global Economic Prospects, 1997)
This 1997 report projects an increase in the growth rate of global input. The improvement is likely to be especially notable for Sub-Saharan Africa, which grew at around 4 percent in 1995 and 1996, and for the developing countries of Europe and Central Asia. Although the East Asian countries will have difficulty maintaining the extremely rapid pace of growth that they have enjoyed in the past decade, they are likely to continue to grow strongly. This year's report focuses on the implications of three important changes in the world economy for developing countries:1) Five large developing and transition economies-China, India, Indonesia, Brazil and Russia-are likely to emerge as key players in the world economy over the next quarter century. This will not only create new opportunities for trade and investment, but will also require significant adjustments in international patterns of specialization for both industrial and developing countries. 2) The expansion of global production networks by multinational enterprises opens new avenues for acquiring international know-how and participating in the gains from international trade. 3) Globalization is also posing broad and more complex policy challenges for governments, especially the proper handling of the costs of adjustment associated with trade liberalization. The report also contains global economic indicators, technical notes, and classification of economies